Best science and technology reference books for young people - Malinowsky, H. Robert (Harold Robert) (Oryx Press, 1991)
Guide lists reference books in physical, applied, and natural sciences and technology for readers from elementary school age to young adults. Includes prices, where reviewed, annotations, and subject terms.